Molybdate reduction to molybdenum blue and growth on polyethylene glycol by Bacillus sp. strain Neni-8 - Rusnam; Rahman, Mohd Fadhil; Gusmanizar, Neni; Yakasai, Hafeez Muhammad; Shukor, Mohd Yunus (Hibiscus Publisher Enterprise, 2021)
The accumulation of heavy metals and xenobiotic compounds in soil and aquatic bodies is caused by inappropriate waste disposal, industrial and mining operations, and excessive use of agricultural pesticides. Bioremediation is a more cost-effective way of removing these pollutants than other approaches. A new molybdenum-reducing bacterium with the ability to grow on a variety of polyethylene glycol (PEG)s has been discovered. Based on biochemical test, the bacterium was partially identified as Bacillus sp. strain Neni-8. Mo-blue production required an optimal pH of between 6.3 and 6.5, and between 30 and 37 oC. The carbon source, D-glucose best supported molybdenum reduction. A narrow requirement for phosphate of between 2.5 and 7.5 mM for molybdenum reduction was seen. Sodium molybdate as a substrate for reduction showed maximal reduction between 20 and 30 mM. The molybdenum blue absorption spectrum indicates that its identity was possibly a reduced phosphomolybdate. Several heavy metals such as silver, mercury, copper and chromium inhibited molybdenum reduction by 67.6, 48.7, 36.8 and 17.4 %, respectively. Bacterial growth modelled using the modified Gompertz model with PEG 600 as the best carbon source predicted a maximum growth rate of 15.4 Ln CFU/ml, a maximum specific growth rate of 0.198 h-1 and a lag period of 10.1 h. The novel characteristics of this bacterium are very useful in future bioremediation works.